Prevalence and Risk Factors of Bovine and Ovine Lungworm Infection at Durame District, Southern Ethiopia. (2nd December 2021) - Fesseha, Haben; Mathewos, Mesfin
Abstract : Background . Lungworms are parasitic nematodes of the order Strongylidae that infect the lungs of cattle and sheep and cause bronchitis or pneumonia. Methods . An abattoir-based cross-sectional study was conducted from November 2018 to April 2019 to determine the comparative prevalence and the possible risk factors of lungworm infection in sheep and cattle of Durame district of Kembata Tembaro zone. For this purpose, a total of 410 animals (209 sheep and 201 cattle) were randomly selected and examined for the presence of different lungworm species using the modified Baermann technique and postmortem examination. The sensitivity and specificity of fecal sample test considering necropsy as reference/gold standard was conducted. Results . Accordingly, the overall prevalence of lungworm infection in sheep and cattle was 24.39%. Dictyocaulus filaria and D. viviparous were the only species of lungworm identified in sheep and cattle with a respective prevalence of 44.02% and 3.98%. Putative risk factors such as species and poor body condition have a significant association (p < 0.05 ) with the occurrence of lungworms in sheep and cattle. The lungworm infection was higher in the young age group (25.30%) and poor body conditioned (32.14%) animals. Season-wise prevalence revealed that a higher lungworm infection was recorded during autumn (32.14%) as compared to winter (22.81%) and spring (16.2%). Most of the sheep and cattle in the current study were heavily (45.0%) and moderately (39.0%) infected with lungworms whereas the rest 16.0% were infected with a low degree of lungworm infection. The specificity, sensitivity, PPV, and NPV of the modified Baermann technique against the gold standard test were 89.4%, 42%, 56.0%, and 82.7%, respectively. Conclusion . The study revealed that lungworm infection is prevalent in sheep and cattle of the study area and that was commonly occurs during autumn and affects poorly conditioned sheep and cattle. Thus, routine and strategic deworming for the control and prevention of lungworms in domestic animals should be recommended to overwhelm the prevalence of lungworm infection.